2017
DOI: 10.1007/s00299-017-2201-5
|View full text |Cite
|
Sign up to set email alerts
|

Oil body biogenesis and biotechnology in legume seeds

Abstract: The seeds of many legume species including soybean, Pongamia pinnata and the model legume Medicago truncatula store considerable oil, apart from protein, in their cotyledons. However, as a group, legume storage strategies are quite variable and provide opportunities for better understanding of carbon partitioning into different storage products. Legumes with their ability to fix nitrogen can also increase the sustainability of agricultural systems. This review integrates the cell biology, biochemistry and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 153 publications
0
30
0
Order By: Relevance
“…The acyl moieties of the phospholipid molecules face inward with the hydrophobic triacylglycerol (TAG) in the matrix and the hydrophilic phospholipid head groups in the cytosol (Tzen et al, 1997). OBs in the seeds of plants are generally circular to ovoid with the average diameter of 0.5-2.5 μm, but the diameter of some OBs can be 2-3 times larger than 2.5 μm, such as in legume seeds (Tzen et al, 1993;Song et al, 2017). Recently, 3D reconstruction analysis showed that the volume of most OBs in Brassica napus seeds were less than 100 μm 3 (Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The acyl moieties of the phospholipid molecules face inward with the hydrophobic triacylglycerol (TAG) in the matrix and the hydrophilic phospholipid head groups in the cytosol (Tzen et al, 1997). OBs in the seeds of plants are generally circular to ovoid with the average diameter of 0.5-2.5 μm, but the diameter of some OBs can be 2-3 times larger than 2.5 μm, such as in legume seeds (Tzen et al, 1993;Song et al, 2017). Recently, 3D reconstruction analysis showed that the volume of most OBs in Brassica napus seeds were less than 100 μm 3 (Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oil bodies are formed via an endoplasmic reticulum (ER)-budding process during seed development ( Sarmiento et al, 1997 ; Hsieh and Huang, 2004 ; Wu et al, 2010 ) and they are detected as early as the heart stage of embryo development ( Siloto et al, 2006 ; Gallardo et al, 2016 ). Besides seeds, oil bodies are found in many different tissues and organs ( Siloto et al, 2006 ; Song et al, 2017 ). Oleosins appear to play an important role in oil seeds, which are the major proteins associated with oil bodies, usually present as two or more isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Ctoleosins have a hydrophobic domain and proline knot motif, and this structure can stabilize the oil body. It is presumed that oleosins accumulate throughout seed development ( Siloto et al, 2006 ; Song et al, 2017 ), and that they stabilize the oil body by steric hindrance and electronegative repulsion ( Tzen et al, 1993 ; Wu et al, 2010 ). Moreover, they prevent oil body coalescence during the process of seed maturation and affect the final size of oil bodies ( Cummins et al, 1993 ; Leprince and Hoekstra, 1998 ; Schmidt and Herman, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences highlighted between M. orbicularis and M. truncatula provide additional approaches into carbon partitioning and the modification of oil content in legumes ( Song et al, 2017 ). The direct testing of the transcription factor GL2 and the GAUT biosynthesis genes can be carried out in M. truncatula , using overexpression or gene knockout using CRISPR/Cas9 ( Luo et al, 2016 ), where there are robust transformation protocols ( Song et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soybean supplies nearly a third of world vegetable oil production ( Graham and Vance, 2003 ). There is a need for more information on the cellular and genetic basis that underlies oil body formation during legume seed development ( Repetto and Gallardo, 2012 ; Wang et al, 2012 ; Song et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%